The Influence of Powerpoint-Based Interactive Teaching Media on Motivation and Learning Outcomes of Social Studies Learning in Class V of SDN Sadeng 03 - Tia, Tia; Tri Astuti; Adinda Assyfa Nurdina; Mezaluna Kharismatika Deazzuri; Farida Lulu Asmara; Jazilatun Nikmah (Lembaga Riset Mutiara Akbar, 2025)
Social studies learning using interactive Powerpoint-based teaching media is one form of technology integration in education that is relevant to the development of the times. This media utilizes visual displays and animations to attract students' attention and facilitate understanding of the material. This study uses a quantitative method with an ex-post facto approach conducted in class V of SD Negeri Sadeng 03. Data collection techniques in this study were interviews with homeroom teachers, documentation, distribution of motivation questionnaires, and student learning outcome data. This study aims to determine the effect of the use of Powerpoint media on learning motivation and student learning achievement in social studies. The results showed that all students had high learning motivation with 55.2% in the